The Effectiveness of the Discovery Learning Model Assisted by Powtoon Animated Video Media on Elementary School Students’ Interest and Learning Outcomes in Social Studies - Suardi, Suardi; Mutmainnah, Mutmainnah; Kaharuddin, Kaharuddin (FKIP - Universitas Riau, 2025)
This study aims to analyze the effectiveness of the Discovery Learning model assisted by Powtoon animated video media on students’ interest and learning outcomes in Social Studies at the elementary school level. A quasi-experimental design with a nonequivalent control group format was employed. The sample consisted of two classes: an experimental group that received instruction using the Discovery Learning model supported by Powtoon animated videos, and a control group that received conventional instruction. Data collection instruments included a learning interest questionnaire and a learning outcomes test, both validated through tests of validity and reliability. Descriptive statistical analysis was used to interpret the data. The results indicated a significant increase in both learning interest and learning outcomes in the experimental group compared to the control group. The integration of the Discovery Learning model with Powtoon animated media proved effective in fostering interactive, motivating, and conceptually enriching learning experiences. These findings suggest that combining a constructivist approach with visual digital media offers an innovative solution for enhancing the quality of Social Studies education in elementary schools.